STUDY OF VIBRIO SPECIES AND ITS OCCURRENCE FREQUENCY IN COLLECTED SEAFOOD SAMPLES - K, Arunagiri; T, Sivakumar; T, Murugan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The intention of the present study was to investigate the prevalence of Vibrio species in seafood samples. Methods: A total of 20 seafood samples include finfishes and crustaceans of marine origin were collected from the local fish market of Kanchipuram, Tamil Nadu. Vibrio colonies were isolated from the samples and identified by cultural, morphological, and biochemical studies. Then, the percentage frequencies of the Vibrio species were intended. Results: A total of 58 Vibrio colonies were isolated from the collected seafood samples. In this, Barracuda fishes contained a higher number of Vibrio colonies (16.07%) followed by Indian mackerel and Crustaceans (12.5%). The foremost three Vibrio species, viz., Vibrio cholerae, Vibrio Parahaemolyticus, and Vibrio alginolyticus were identified by studying cultural, morphological, and biochemical characteristics, and the incidence percentage was found as 22.41%, 17.24%, and 12.07%, respectively, from the total Vibrio colonies isolated. Conclusion: Thus, these results revealed that the pathogenic Vibrio species of V. cholerae and V. parahaemolyticus was found higher percentages in collected seafoods. Keywords: Seafood, Vibrios, Finfish, Vibrio parahaemolyticus.